'Mixed blessings': parental religiousness, parenting, and child adjustment in global perspective. (28th February 2017) - Bornstein, Marc H.; Putnick, Diane L.; Lansford, Jennifer E.; Al‐Hassan, Suha M.; Bacchini, Dario; Bombi, Anna Silvia; Chang, Lei; Deater‐Deckard, Kirby; Di Giunta, Laura; Dodge, Kenneth A.; Malone, Patrick S.; Oburu, Paul; et al.
Abstract : Background: Most studies of the effects of parental religiousness on parenting and child development focus on a particular religion or cultural group, which limits generalizations that can be made about the effects of parental religiousness on family life. Methods: We assessed the associations among parental religiousness, parenting, and children's adjustment in a 3‐year longitudinal investigation of 1, 198 families from nine countries. We included four religions (Catholicism, Protestantism, Buddhism, and Islam) plus unaffiliated parents, two positive (efficacy and warmth) and two negative (control and rejection) parenting practices, and two positive (social competence and school performance) and two negative (internalizing and externalizing) child outcomes. Parents and children were informants. Results: Greater parent religiousness had both positive and negative associations with parenting and child adjustment. Greater parent religiousness when children were age 8 was associated with higher parental efficacy at age 9 and, in turn, children's better social competence and school performance and fewer child internalizing and externalizing problems at age 10. However, greater parent religiousness at age 8 was also associated with more parental control at age 9, which in turn was associated with more child internalizing and externalizing problems at age 10. Parental warmth and rejection had inconsistent relations with parental religiousness and child outcomes depending on the informant. With a few exceptions, similar patterns of results held for all four religions and the unaffiliated, nine sites, mothers and fathers, girls and boys, and controlling for demographic covariates. Conclusions: Parents and children agree that parental religiousness is associated with more controlling parenting and, in turn, increased child problem behaviors. However, children see religiousness as related to parental rejection, whereas parents see religiousness as related to parental efficacy and warmth, which have different associations with child functioning. Studying both parent and child views of religiousness and parenting are important to understand the effects of parental religiousness on parents and children.